Traditional Chinese Medicine Interventions in the Rehabilitation of Cognitive and Motor Function in Patients With Stroke: An Overview and Evidence Map - Choi, Tae-Young; Jun, Ji Hee; Lee, Hye Won; Yun, Jong-Min; Joo, Min Cheol; Lee, Myeong Soo (Frontiers in Neurology, 2022)
Evidence mapping of systematic reviews (SRs) systematically and comprehensively identifies, organizes, and summarizes the distribution of scientific evidence in a field. The aim of this evidence map is to provide a synopsis of best clinical practices and interventions in stroke rehabilitative care and to identify areas with a paucity of evidence to guide future research. PubMed, EMBASE, CDSR, CNKI and six Korean databases were searched for SRs evaluating the effectiveness of any intervention in stroke rehabilitation through October 2021. The quality of the SRs was assessed using AMSTAR-2. The bubble plot graphically displays clinical topics, number of articles, number of total populations, confidence, and effectiveness. Ninety-five randomized controlled trials (RCTs) were identified; however, after methodological analysis, only 48 had sufficient quality to be included. Forty-eight SRs were included in the evidence mapping. The overall search identified SRs from 2015 to 2021. Four SRs focused on poststroke cognitive impairment, whereas the other forty-four SRs focused on poststroke motor function. Nineteen different traditional Chinese medicine (TCM) intervention modalities were included. Acupuncture was the most commonly used. Overall, the quality of the included SRs was low or very low. Most SRs reached the conclusion that TCM interventions may have potential benefits in stroke rehabilitation. In particular, the results were more promising when acupuncture was used for shoulder hand pain. However, the identified reviews cautioned that firm conclusions cannot be drawn. The evidence map provides a visual overview of the research volume and content involving TCM interventions in stroke rehabilitation. Evidence mapping can facilitate the process of knowledge translation from scientific findings to researchers and policy makers and possibly reduce waste in research.